Happiness at work, from the dimensions of well-being - Oliveira, Elizangela de Jesus; Ferreira, Rosivan Cardoso; Lopes, Rute Holanda; Andrade, Darly; Alves, Gleica Soyan Barbosa (Brazilian Journal of Production Engineering, 2020)
This paper aimed to explain, from well-being dimensions, which are the predictors of happiness at work and how they are manifested, in the perception of the employees of a service company, located in Minas Gerais. We aimed to fill an academic literature gap, once we did not find studies correlating the eudaimonic vision (psychological well-being) and the hedonic vision (subjective well-being) with the well-being at work, in order to characterize happiness at work.We realized a descriptive and quantitative case study. Data were collected through a questionnaire with three scales for measuring Psychological Well-being, the Subjective Well-being and Well-being at work. We obtained a sample of 121 employees, with a confidence level of 95% and a sampling error of 5%. Data was analyzed by means of univariate statistics and structural equation modeling.The results revealed that subjective well-being is positively correlated with psychological well-being that is positively correlated with well-being at work. This result partially confirms the proposed model.Well-being at work can be positively or negatively impacted, depending on individuals’ emotions and/or feelings. The greater the experience of positive feelings and the smaller of negatives feelings, the greater the well-being at work and, consequently, happiness at work. For future research, we suggest to investigate more deeply the relationship between BEP and BET, since we did not evidenced correlation between these constructs in this study, although this relation is postulated by the literature.
Keywords: happiness at work; well-being at work; psychological well-being; subjective well-being